The Educating Children With Love - Novi Cahya Dewi; Patriana Patriana (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Affection is the main basic component in the education process and the formation of children's character or morals. Parents who always educate their children with love and affection will make the learning atmosphere in the household very pleasant for children. Children never get bored to absorb every lesson given. Because there is no better way to captivate a child's heart and win his trust than to develop a sense of love and affection by his parents. With love and affection the atmosphere of the house will be a very pleasant place for children and all residents. So that the house becomes a place to live and gather all joy, peace and politeness. A house filled with rays of love and affection will be a place where honesty and all the qualities of goodness and happiness reside. The importance of parental love for children requires maximum effort from both parents in giving these expressions of affection to children, so the role of parents is very necessary in educating children at a young age.